2017
DOI: 10.2196/jmir.6962
|View full text |Cite
|
Sign up to set email alerts
|

Readability Formulas and User Perceptions of Electronic Health Records Difficulty: A Corpus Study

Abstract: BackgroundElectronic health records (EHRs) are a rich resource for developing applications to engage patients and foster patient activation, thus holding a strong potential to enhance patient-centered care. Studies have shown that providing patients with access to their own EHR notes may improve the understanding of their own clinical conditions and treatments, leading to improved health care outcomes. However, the highly technical language in EHR notes impedes patients’ comprehension. Numerous studies have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Patient-centered care has been found to positively impact a number of measures such as patient compliance, satisfaction, and health outcomes [ 13 ]. Given the increasing rates of EHR adoption, it is critical to provide physicians with formal education on patient-centered EHR communication skills; however, finding the time to teach these skills in crowded training programs poses a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-centered care has been found to positively impact a number of measures such as patient compliance, satisfaction, and health outcomes [ 13 ]. Given the increasing rates of EHR adoption, it is critical to provide physicians with formal education on patient-centered EHR communication skills; however, finding the time to teach these skills in crowded training programs poses a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patient satisfaction with the interaction and the perception of their overall quality of care may be decreased [ 4 - 11 ]. Similarly, best practices for patient-physician EHR interactions exist, and research shows that when EHRs are integrated in a patient-centered manner, physicians can foster patient activation and engagement by improving communication, enhancing patient understanding of their medical conditions, and promoting increased shared decision making [ 1 , 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that this percentage correlates significantly with the level of understanding as indicated by users but not with the readability formula levels. On the same line, Zheng & Yu (2017) found that the correlations of readability predictions and laypeople's perceptions were weak. Their study with English texts explored the relationship between several readability formulas and the laypeople's perceived difficulty on two genres of text: general health information and electronic health record (EHR) notes.…”
Section: Previous Work: Layficationmentioning
confidence: 90%
“…For example, Becker reported that the majority of health Web sites are not well designed for the elderly [21], while Stossel et al found that health education material on the Web is not written at an adequate reading level [18]. Zheng and Yu have reported on the readability of electronic health records compared to Wikipedia pages related to diabetes and found that readability measures often do not align with user ratings of readability [22]. A common finding of these studies is that, in general, health content available on Web pages is often hard to understand by the general public; this includes content that is retrieved in topranked positions by current commercial search engines [4,5,6,7,8,9].…”
Section: Related Workmentioning
confidence: 99%